CLOUD BASED LEARNING ENVIRONMENT FORMATION FOR MATHEMATICS DISCIPLINES LEARNING USING THE SAGEMATHCLOUD (GUIDELINES) - Shyshkina М.П.; Popel М.В. (Journal of Information Technologies in Education (ITE), 2016)
The article is devoted to the problems of the cloud-based systems use in the educational process of pedagogical universities. The types of the cloud-based services for mathematics disciplines learning in the structure of the cloud-based learning environment are revealed; the model of the cloud-based learning environment of pedagogical university is proposed; the prospects for computer mathematics systems (SCM) development and use in the aspect of the cloudy based learning environment formation are considered. The pedagogical features of the SageMathCloud use, as a tool for mathematics disciplines learning are revealed. The instructional aspects of SageMathCloud use (how to get started, the creation of lecture demonstrations and dynamic models, the organization of collective work) are revealed. The guidelines for the use of the cloud-based systems in the process of mathematics disciplines learning are proposed. The aim of the article: To carry out the theoretical analysis and provide guidelines for the use of the SageMathCloud in the process of mathematics disciplines learning. The object of research: the process of the cloud-based learning environment for learning mathematics disciplines formation and use in the pedagogical university. The subject of research: The methodical aspects of the SageMathCloud use as a component of the cloud-based environment for learning mathematics disciplines. The research results: the theoretical framework and guidelines for the SageMathCloud use as a tool for learning mathematics disciplines is grounded. Conclusions: the cloud-based environment formation using the SageMathCloud is methodologically appropriate, it will improve access to learning software and electronic resources, improve the process of learning mathematics disciplines, achieving better result.